2008
DOI: 10.1016/j.csr.2008.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Sediment dispersal from a typical Mediterranean flood: The Têt River, Gulf of Lions

Abstract: This paper describes an integrated study of a typical Mediterranean flood event in the Gulf of Lions. A flood with a 5-year return interval occurred in the Têt River basin and adjacent inner-shelf in the Gulf of Lions, northwest Mediterranean, during April 2004. Data were collected during this flood as part of event-response investigations of the EU-funded Eurostrataform (European Margin Strata Formation) project. Southeasterly storm winds led to a flood which directly modified the inner-shelf hydrodynamics. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 46 publications
4
40
0
Order By: Relevance
“…Locally, the Canet harbour in the south of the domain disturbs the longshore drift by shifting it offshore. These results are consistent with the development of sand spits growing northwards at river mouths, sand bars and harbours, as observed by Delpont and Motti (1994); Bourrin et al (2008) and in the LiDAR bathymetry. Downstream from the harbour, since the beginning of the storm, a cyclonic eddy and a return current along the northern breakwater of the harbour are generated, as discussed by Trampenau et al (2004).…”
Section: Current In the Surf Zonesupporting
confidence: 79%
See 2 more Smart Citations
“…Locally, the Canet harbour in the south of the domain disturbs the longshore drift by shifting it offshore. These results are consistent with the development of sand spits growing northwards at river mouths, sand bars and harbours, as observed by Delpont and Motti (1994); Bourrin et al (2008) and in the LiDAR bathymetry. Downstream from the harbour, since the beginning of the storm, a cyclonic eddy and a return current along the northern breakwater of the harbour are generated, as discussed by Trampenau et al (2004).…”
Section: Current In the Surf Zonesupporting
confidence: 79%
“…A recent LiDAR (Light Detection and Ranging) survey (Fig. 8) shows a sand spit developing northwards of the breakwaters of the Canet-en-Roussillon harbor, followed by a deep pit, as observed by Bourrin et al (2008). Thereafter, complex double crescentic sandbar systems, classified as low tide terraces (LTT) by Aleman et al (2011), are observed.…”
Section: Coastal Circulation and The Têt Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the Mediterranean shore is characterized by numerous coastal rivers that discharge significant amounts of water and sediment, mainly during the occurrence of short but violent flash flood events (Serrat et al, 2001;Bourrin et al, 2008). Several studies on the Rhône River have shown that the terrestrial particulate organic matter (POM) may be qualified as enough fresh, labile and modern POM to drive degradation processes (Bourgeois et al, 2011;Cathalot et al, 2010) and to sustain dense macrofaunal communities in surface sediments of the prodelta (Darnaude et al, 2004;Hermand et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Not all tempestites comprise all these features, and they may also be observed in offshore tsunami deposits . Flash floods can comprise a large percentage of a river's yearly discharge and can form hyperpycnal flows due to high suspension load (Mulder et al, 2003;Bourrin et al, 2008). These criteria have also been established for tsunami backwash flows (Le Roux and Vargas, 2005).…”
Section: Introductionmentioning
confidence: 99%